Seasonal Clinical Indicators of Karakul Sheep Raised in Various Ecological Regions - Jiyanmuradova Shakhlo Khamdamovna (American Journal of Biology and Natural Sciences, 2024)
This article presents information on the study of body temperature, heart rate, and respiratory rate of Karakul sheep raised in various ecological regions, based on comparative analyses by seasons.